New Facility for Membrane Fouling Investigations under Customizable Hydrodynamics: Validation and Preliminary Experiments with Pulsating Cross-Flow - Roberto Bert; Costantino Manes; Alberto Tiraferri (Membranes, 2022)
Flux reduction induced by fouling is arguably the most adverse phenomenon in membrane-based separation systems. In this respect, many laboratory-scale filtration studies have shown that an appropriate use of hydrodynamic perturbations can improve both performance and durability of the membrane; however, to fully understand and hence appropriately exploit such effects, it is necessary to understand the underpinning flow processes. Towards this end, in this work we propose and validate a new module-scale laboratory facility with the aim of investigating, at very well-controlled flow conditions, how hydrodynamics affects mass transport phenomena at the feed/membrane interface. The proposed facility was designed to obtain a fully developed and uniform flow inside the test section and to impose both steady and pulsating flow conditions. The walls of the facility were made transparent to grant optical accessibility to the flow. In this paper, we discuss data coming from particle image velocimetry (PIV) measurements and preliminary ultrafiltration tests both under steady and pulsating flow conditions. PIV data indicate that the proposed facility allows for excellent flow control from a purely hydrodynamic standpoint. Results from filtration tests provide promising results pointing towards pulsating flows as a viable technique to reduce fouling in membrane systems.